2019
DOI: 10.1101/698001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Astaxanthin extends lifespan via altered biogenesis of the mitochondrial respiratory chain complex III

Abstract: Astaxanthin is a keto-carotenoid produced in some bacteria and algae, which has very important industrial applications (i.e., in cosmetics, coloring additive in aquaculture and as a dietary supplement for human). Here, we analyzed the molecular basis of Astaxanthin-mediated prolongevity in the model organism, Caenorhabditis elegans. The increased lifespan effects of Astaxanthin are restricted in C. elegans to the adult phase and are uninfluenced by various other carotenoids tested. Genetic analyses indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Carotene lycopene had no effects on C. elegans lifespan parameters [ 348 ]. At the same time, pure synthesized lycopene at a dose of 7.5 ppm increased the mean lifespan of both D. melanogaster males and females by 4.8–8.1% as well as the maximum lifespan of females by 4.8% [ 345 ].…”
Section: Terpenoids As Potential Geroprotectorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Carotene lycopene had no effects on C. elegans lifespan parameters [ 348 ]. At the same time, pure synthesized lycopene at a dose of 7.5 ppm increased the mean lifespan of both D. melanogaster males and females by 4.8–8.1% as well as the maximum lifespan of females by 4.8% [ 345 ].…”
Section: Terpenoids As Potential Geroprotectorsmentioning
confidence: 99%
“…Astaxanthin in concentrations 0.1–1 mM also increased the mean lifespan of wild-type C. elegans up to 31% [ 351 ]. It was shown that the positive effects on C. elegans lifespan parameters were observed only if the compound was fed to animals throughout their entire life or only at adult stage [ 348 ]. No effects were found, when astaxanthin has been fed to worms only from the larval L1 stage until adulthood.…”
Section: Terpenoids As Potential Geroprotectorsmentioning
confidence: 99%
See 3 more Smart Citations